Research on the spatial characteristics of urban integration from multi-dimensions: A case study in the Guangzhou-Qingyuan metropolitan area - Tang, Bo; Huang, Zhangdi (Frontiers in Earth Science, 2023)
The urban integration of metropolitan areas is an important embodiment of the high-quality development of urban agglomerations. Using the data of 2012–2020 NPP-VIIRS night light, social economy, OSM, and Baidu migration, etc., we explore the characteristics of Guangzhou-Qingyuan’s urban integration from four dimensions, such as economic development, industrial structure, transportation facilities, and public services using the methods such as geographical information method, commodity urban integration index, industrial structure similarity index, etc. The research results are as follows: The spatial pattern of economic development in the Guangzhou-Qingyuan differs greatly, but with the advancement of the integration process, regional economic exchanges have been enhanced; the commodity urban integration index is on the increase, the degree of market segmentation is gradually shrinking, and the level of commodity market urban integration is constantly improving. The industrial integration of the Guang-Qing area has an obvious effect. Although the index of similarity of industrial structure is high, there is a trend of gradual convergence and coordination; the leading industries are not the same, and the industrial demands are complementary to realize the coordinated development of the industry. The trend of the transportation urban integration in Guangzhou-Qingyuan is obvious, and the road network develops rapidly, but the travel time between the two cities is still relatively long. The transportation accessibility presents a circle-layer structure on the whole, and the transportation accessibility at the boundary area between the two cities has been greatly improved. Due to the close links between the historical foundation and social culture, inter-city people flow frequently, the public service facilities in Guangzhou-Qingyuan show an obvious trend of urban integration, but the relevant infrastructure needs to be improved urgently.